Governance of offshore freshwater resources - Martin-Nagle, Renee (Legal aspects of sustainable development, 2020)
"In Governance of Offshore Freshwater Resources Renée Martin-Nagle presents the scientific proof for vast quantities of freshwater in the seabeds, explains the socio-economic factors that will lead to development of the resource, and examines the international law principles and regimes that would guide policymakers in designing a governance system for offshore freshwater. Pursuant to the law of the sea, coastal states have sovereign rights to seabed resources within their exclusive economic zones. Offshore hydrocarbon development has produced customary practices for cooperation that were inspired by international water law and that could serve as a template for governing transboundary offshore freshwater. Given the vital nature of freshwater, equitable distribution of this new resource and its benefits should be considered"--